JMJD1C-regulated lipid synthesis contributes to the maintenance of MLL-rearranged acute myeloid leukemia. Issue 9 (29th July 2022) - Qi, Daoxin; Wang, Jialing; Zhao, Yao; Yang, Yong; Wang, Yishu; Wang, Haihua; Wang, Lin; Wang, Zhanju; Xu, Xin; Hu, Zhenbo
Abstract: Mixed Lineage Leukemia rearranged acute myeloid leukemia ( MLL r AML) predicts a poor prognosis. Histone demethylase JMJD1C is a potential druggable target of MLL r AML. However, little is known about how JMJD1C contributes to MLL r AML. Here we found that JMJD1C regulates lipid synthesis-associated genes including FADS2, SCD in MLL r AML cells. Lipid synthesis-associated protein FABP5 was identified as a specific interacting protein of JMJD1C and binds to the jumonji domain of JMJD1C. FABP5 also regulates JMJD1C mRNA and protein expression. JDI-10, a small molecular inhibitor of JMJD1C identified by us, represses MLL r AML cells, induces apoptosis, and decreases JMJD1C-regulated lipid synthesis genes. Moreover, JDI-10 mediated suppression of MLL r AML cells can be rescued by palmitic acid, oleic acid, or recombinant FABP5. In summary, we identified that JMJD1C-regulated lipid synthesis contributes to the maintenance of MLL r AML. Lipid synthesis repression may represent a new direction for the treatment of MLL r AML.